Structures of SAS-6 coiled coil hold implications for the polarity of the centriolar cartwheel - Kantsadi, AL; Hatzopoulos, GN; Gönczy, P; Vakonakis, I (Cell Press, 2022)
Centrioles are eukaryotic organelles that template the formation of cilia and flagella, as well as organize the microtubule network and the mitotic spindle in animal cells. Centrioles have proximal-distal polarity and a 9-fold radial symmetry imparted by a likewise symmetrical central scaffold, the cartwheel. The spindle assembly abnormal protein 6 (SAS-6) self-assembles into 9-fold radially symmetric ring-shaped oligomers that stack via an unknown mechanism to form the cartwheel. Here, we uncover a homo-oligomerization interaction mediated by the coiled-coil domain of SAS-6. Crystallographic structures of Chlamydomonas reinhardtii SAS-6 coiled-coil complexes suggest this interaction is asymmetric, thereby imparting polarity to the cartwheel. Using a cryoelectron microscopy (cryo-EM) reconstitution assay, we demonstrate that amino acid substitutions disrupting this asymmetric association also impair SAS-6 ring stacking. Our work raises the possibility that the asymmetric interaction inherent to SAS-6 coiled-coil provides a polar element for cartwheel assembly, which may assist the establishment of the centriolar proximal-distal axis.